Вчення про форму Української держави в теоретичній спадщині М.Ю. Шаповала - Габінет, Д.А. (Держава і право, 2011)
Проаналізовано
становлення
та еволюцію
поглядів
М.Ю. Шаповала
на форму
державного
правління, політичного
режиму
та державного
устрою
майбутньої
незалежної
Української
держави. Проанализировано
становление
и эволюцию
взглядов
Н.Ю. Шаповала
на форму
государственного
правления,
политического
режима
и государственного
устройства
будущего
независимого
Украинского
государства. Problems connected with a creative heritage of N. Yu. Shapoval, the active participant of
the Ukrainian national movement of the first half of XX century are considered in the article.
The formation and evolution of views of N. Yu. Shapoval on the form of government, the state
regime and the state system form of the future independent Ukrainian state is analyzed by the
author.